PJMHS 2022
DOI: 10.53350/pjmhs221610633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mirror Therapy for Improving the Motor Function of Upper and Lower Extremities in Patients with Stroke – A Quasi Experimental Study

Abstract: Background: Stroke is defined as the rapid onset of focused or generalized disturbance of cerebral functions that lasts more than 24 hours. Speech issues and weakness on one side of the body are typical stroke signs and symptoms. Patients with upper limb disability following a stroke were unable to carry out particular gripping and manipulating tasks. Objective: Determine Effects of Mirror Therapy for Improving the Motor Function of Upper and Lower Extremities in Patients with Stroke Material and Methods: A q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For data synthesis, the authors summarized the article based on the research subject, age and sex of participants, the type of intervention given (both from frequency, duration, and tools to measure the effectiveness of the intervention), the effectiveness of the intervention, and the conclusion. This research instrument uses Standard Operating Procedures Mirror Therapy, MMT scale (Manual Muscle Test), Visual Scale (VIS), Fulg Major Assessment (FMA), Barthel Index (Istianah et al, 2020) (Kiran et al, 2022) (Ginting et al, 2022) (Hamzah et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For data synthesis, the authors summarized the article based on the research subject, age and sex of participants, the type of intervention given (both from frequency, duration, and tools to measure the effectiveness of the intervention), the effectiveness of the intervention, and the conclusion. This research instrument uses Standard Operating Procedures Mirror Therapy, MMT scale (Manual Muscle Test), Visual Scale (VIS), Fulg Major Assessment (FMA), Barthel Index (Istianah et al, 2020) (Kiran et al, 2022) (Ginting et al, 2022) (Hamzah et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…resulted in a significant difference between the average scores of the two groups. It was found that PNF and MT were effective in increasing motor function scores but MT was found to have a better effect compared to PNF (Kiran et al, 2022).…”
Section: Table 2 Dosage Intervention Mirror Therapymentioning
confidence: 95%